Sosialisasi Anti Korupsi Dan Mekanisme Pembuatan Peraturan Desa Pada Desa Wisata Tiwingan Lama Kecamatan Aranio Kabupaten Banjar - Budi Suryadi; Angga Ramadanu; Bayu Febrian; Fazrul Huda; Hena Selvia; Juna Indah; Olivia Febrianti; Zaky Yasin (Journal of Empowerment and Community Service (JECSR), 2021)
Corruption is very difficult to eliminate in officials in the Indonesian state. The Corruption Eradication Commission as an institution tasked with eradicating corruption is still not optimal. The Corruption Eradication Commission noted that as many as 300 regional heads had been involved in corruption cases since the direct election of regional heads in 2005. Currently, the highest to the smallest officials, namely the village head, also have corruption. In addition, there are still many acts of corruption committed by village heads in Indonesia. Therefore, it is necessary to socialize the dangers of acts of corruption. In addition to criminal acts of corruption committed by the village government, the most crucial thing in village government is village regulations, so village heads or village government officials must understand the flow of making village regulations, especially if the village is a tourist village.